Pemanfaatan Media Teknologi Informasi Komunikasi Dalam Peningkatan Kinerja Guru Pendidikan Agama Islam - Sufrinsyah Pasaribu (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2019)
This article aims to analyze the use of Information and Communication Technology, the media, the use of information and communication technology to improve the performance of PAI teachers in learning Islamic Education in SMA Negeri 1 Matauli Pandan, Central Tapanuli Regency through qualitative research with descriptive analysis. The results of the study contained the use of Information and Communication Technology in Islamic Education in SMA 1 Plus Matauli Pandan, Central Tapanuli Regency, using ICT as a medium that was sufficient to help the performance of PAI teachers so that the results were significant.